Age, Sex, and Nest Success of Translocated Mountain Quail in Oregon, 2001–2010 - David A. Budeau; Tim L. Hiller (National Quail Symposium Proceedings, 2017)
We trapped mountain quail (Oreortyx pictus) from relatively abundant populations in southwestern Oregon for re-introduction or augmentation in areas of central and eastern Oregon where they were rare or extirpated. We captured 2,596 mountain quail during 2001–2010 using treadle-style traps, of which 1,430 were released in Oregon; the remaining birds were transferred to Idaho, Nevada, and Washington. Yearlings (hatch-year) comprised 69.6% of the total (n 1⁄4 2,596). Analysis of nuclear DNA from 850 captured quail revealed 50.5% were male. We radiomarked 800 (55.9%) of the quail released in Oregon and monitored them to estimate reproductive success. We located 150 nests in Oregon; at least 1 egg hatched in 110 (73.3%) nests. Average (6 SE) clutch size was 10.2 6 0.2 eggs and average number of chicks hatched from successful nests was 8.3 6 0.3. Sixty-eight nests (45.3%) were incubated exclusively by males, 78 (52.0%) exclusively by females, and 4 (2.7%) by birds of unknown gender. Males incubated slightly larger clutches (11.0 6 0.3) and hatched more eggs than females (5.5 6 0.5). Males also regularly contributed to brood-rearing. The reproductive effort and nest success of translocated mountain quail was comparable to native populations in Oregon. Translocations may be an effective means of restoring mountain quail populations that have been extirpated or augmenting populations that have substantially declined.
Keywords: clutch size; mountain quail; nest success; Oregon; Oreortyx pictus; translocation